Epicardial adipose tissue volume a diagnostic study for independent predicting disorder of circadian rhythm of blood pressure in patients with essential hypertension - Zhou, L; Deng, Y; Gong, J; Chen, X; Zhang, Q; Wang, J (Cellular and Molecular Biology, 2016)
The aim of the study was to determine whether epicardial adipose tissue volume (EATV), a new cardiometabolic risk factor, is associated with circadian changes of blood pressure (BP) in patients with newly diagnosed essential hypertension. Ninety patients with newly diagnosed essential hypertension underwent ambulatory blood pressure monitoring for 24 h. EATV was measured using cardiac computed tomography. These patients were categorized into three groups according to their BP patterns (group 1, n=46, dipper hypertension, also called normal pattern; group 2, n=24, non-dipper hypertension; group 3, n=20, anti-dipper hypertension; group 2 and 3 are also called abnormal pattern). Data were collected retrospectively and compared between hypertensive patients with normal pattern and abnormal pattern. The normal pattern hypertensive patient had significant lower mean EATV and BP ((EATV, 91.3±29.4 cm3) than those of abnormal pattern patients including group 2 (EATV, 116.2±31.06cm3, <0.01) and group 3 (EATV, 124.8±28.5cm3, P<0.01). Mean systolic BP over 24 h (BPs24) and mean diastolic BP over 24 h (BPd24) of group 1 (BPs24, 135.7 ± 12.6 mmHg; BPd24, 83.6 ± 10.6 mmHg) were significantly lower than those of group 2 (BPs24, 150.1± 17.6 mmHg, P<0.01; BPd24, 93.2 ± 16.5 mmHg, P<0.01) and group 3 (BPs24, 154.1 ± 16.6mmHg, P<0.01; BPd24, 93.8 ± 17.5 mmHg; P<0.01). Bivariate correlation analysis showed that correlation coefficient of EATV with abnormal blood pressure mode was 0.500 (p<0.001), partial correlation coefficient after adjustment for waist circumference and body mass index was 0.469 (p<0.001). When multivariate backward logistic regression analysis was performed to assess the correlation of BP pattern with EAT volume, it showed that the prevalence of abnormal BP pattern (non-dipper and anti-dipper BP pattern) increased by 1.54 times after adjusting for age and gender per additional 10 cm3 of EAT volume. Receiver operating characteristic curve for EAT alone indicated that the cutoff value of 95.17cm3 had the best performance in predicting abnormal BP pattern with a sensitivity of 75.0% and a specificity of 72.7%. EATV was elevated in newly diagnosed and untreated patients with non-dipper hypertension and anti-dipper hypertension. EATV measured by cardiac computed tomography can be used to indicate the increased risk of circadian rhythm of blood pressure.